Pengaruh Hexagon Fraud Theory Terhadap Kecurangan Laporan Penjualan Oleh Karyawan Pada Pt. Indomarco Prismatama - Putra, Moch. Rohiki Santoso; Awalina, Putri; Wahyudi, Moch. (Jurnal Ilmiah Cendekia Akuntansi; Vol 10 No 3 (2025): JuliDO - 10.32503/cendekiaakuntansi.v10i3.8112, 2025)
Abstraction This study aims to determine the effect of the Hexagon Fraud Theory on employee fraudulent sales reports at PT Indomarco Prismatama. This research is quantitative. Data were obtained through primary and secondary data. The population was comprised of PT Indomarco Prismatama employees. A sample of 58 employees was selected using saturated sampling. The analytical techniques used were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the study show that Pressure has a positive and significant effect on fraudulent sales reports with a sig value of 0.002 <0.05. Capability has a positive and significant effect on fraudulent sales reports with a sig value of 0.027 <0.05. Collusion has a positive and significant effect on fraudulent sales reports with a sig value of 0.002 <0.05. Opportunity has a positive and significant effect on fraudulent sales reports with a sig value of 0.021 <0.05. Rationalization has a positive and significant effect on fraudulent sales reports with a sig value of 0.000 <0.05. Arrogance has a positive and significant effect on fraudulent sales reports with a sig value of 0.009 <0.05. Pressure, capability, collusion, opportunity, rationalization and arrogance have a positive and significant effect on fraudulent sales reports with a sig value of 0.000 <0.05.   Keywords: Pressure, capability, collusion, opportunity, rationalization and arrogance, sales report ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh Hexagon Fraud Theory terhadap kecurangan laporan penjualan oleh karyawan pada PT Indomarco Prismatama. Jenis penelitian ini adalah penelitian kuantitatif. Data penelitian ini diperoleh melalui data primer dan sekunder. Populasi dalam penelitian ini adalah Karyawan pada PT Indomarco Prismatama. Sampel dalam penelitian ini sebanyak 58 karyawan dengan Teknik pengambilan sampel menggunakan sampling jenuh. Tehnik analisis yang digunakan yaitu uji validitas, uji reliabilitas, uji asumsi klasik, analisis regresi linier berganda dan uji hipotesis. Hasil penelitian menunjukan bahwa Pressure berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,002 < 0,05. Capability berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,027 < 0,05. Collusiaon berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,002 < 0,05. Opportunity berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,021 < 0,05. Rationalization berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,000 < 0,05. Aroganze berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,009 < 0,05. Pressure, capability, collusion, opportunity, rationalization dan aroganze berpengaruh positif dan signifikan terhadap kecurangan laporan penjualan dengan nilai sig 0,000 < 0,05.   Kata kunci: Pressure, capability, collusion, opportunity, rationalization dan                      aroganze, Laporan penjualan